Detecção de anticorpos específicos IgA e IgG em amostras pareadas de soro e leite na Estrongiloidíase humana - Ferreira, Daniela Marques de Lima Mota (2005)
Strongyloidiasis, caused by the nematode Strongyloides stercoralis, is one of the major parasite infections in humans, distributed wordwilde, with difficulties in diagnosis. Breastfeeding may offer a potential protection against the infection. The objective of the study was to detect specific 5. stercoralis IgA and IgG antibodies in serum and breast milk samples of 90 lactating women from Clinics Hospital of Federal University of Uberlândia using indirect fluorescent antibody test (IFAT) and enzyme-linked immunosorbent assay (ELISA). Subjects were divided in two groups according to the detection of specific £ stercoralis IgG antibody by ELISA in serum samples: group I - positive specific IgG antibody (n = 36)-group II - negative specific IgG antibody (n = 54). Comparing both groups positivity was greater in group I to detect specific £ stercoralis IgA and IgG antibodies using both immunological methods. Positivity for specific IgA antibody in group I was 41.7% by IFAT and 44.4% by ELISA in serum samples with a concurrence of 86.1% (P < 0.0001). In breast milk samples positivity for specific IgA antibody was 63.9% using IFAT and 61.1% using ELISA with a concurrence of 69.4% (P < 0.001). Considering the detection of specific IgG antibody in group I, positivity in serum samples was 94.4% in IFAT and 100% in ELISA with a concurrence of 94.4% (P < 0.0001). In breast milk samples positiviy for specific IgG antibody was 63.9% in IFAT and 44.4% in ELISA with a concurrence of 52.8% (P > 0 05) Specific £ stercoralis IgA and IgG antibodies were detected in serum and breast milk samples using IFAT and ELISA and both tests showed concordance in detecting specific IgA antibody in serum and breast milk samples and in detecting specific IgG antibody in serum samples.